AMERICAN TRANSCENDENTALISM TO FIND DIVINE IN THE CELESTINE PROPHECY AND THE TENTH INSIGHT BY JAMES REDFIELD - RAFSANJANI, GEOVANDILLA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords:American Transcendentalism, Manifestation of Effort, The Emerging Spirituality Energy, The Celestine Prophecy, The Tenth Insight.The social phenomena in America are used by some authors to create thestory of a literary work in order to make it representable in appreciation some societies in particular era. James Redfield is one of American authors in 1990’s who interested in describing the human potential movement and turned it totheories about intuitions, the historical perspective background of the emergingspirituality that discussed in his novels, The Celestine Prophecy and The Tenth Insight.Transcendentalism approach is applied in this study because it deals with theidea of a development on human thoughts. This approach brings to the use ofDivine value which leads to the intuiton, the clue of nature, historical perspective,relating with others, and holding vision by God for humans who seek theirdestiny. John Woodson as the main character on the novel is used as therepresentative objectto study because his personal experience on his journey andadventure towards his efforts to find the ancient manuscript phenomenon thathappens in Peru. The result of this study reveals that the existence of the two roots ofAmerican Philoshophy known as American Transcendentalism, are stillpreserved. John Woodson succesfully manifests the goals of AmericanTranscendentalism that certainly taken from spirituality values’s idea through hisefforts told in the novels. This result leads to the comprehension of how AmericanTranscendentalism influence American’s mind in fulfilling his purpose life orachievement.